2020
DOI: 10.1093/jn/nxz184
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Insulin Resistance Are Inversely Associated with Serum and Adipose Tissue Carotenoid Concentrations in Adults

Abstract: Background Low tissue concentrations of carotenoids have been suggested to contribute to insulin resistance in obesity. Objectives The objectives of the study were to 1) evaluate the relations of adipose tissue and serum carotenoids with body fat, abdominal fat distribution, muscle, adipose tissue and liver insulin resistance, and dietary intake; 2) evaluate the relations and distributions of carotenoids detected in adipose t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 50 publications
4
47
0
Order By: Relevance
“…For example, in our previous study [ 8 ], high BMI was associated with low serum concentration of total carotenoid, whereas Suzuki et al have reported an association between high waist circumference and low serum β-carotene levels in females [ 14 ]. Carotenoid concentrations in adipose tissue have also been measured, which have been shown to be related to waist circumference [ 15 ]. Sato et al reported that there were misjudgments of more than 20% when they judged whether the VFA was equal to or larger than 100 cm 2 using the criteria of waist circumference [ 16 ], so measuring VFA itself rather than waist circumference is considered preferable for subsequent disease prevention.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in our previous study [ 8 ], high BMI was associated with low serum concentration of total carotenoid, whereas Suzuki et al have reported an association between high waist circumference and low serum β-carotene levels in females [ 14 ]. Carotenoid concentrations in adipose tissue have also been measured, which have been shown to be related to waist circumference [ 15 ]. Sato et al reported that there were misjudgments of more than 20% when they judged whether the VFA was equal to or larger than 100 cm 2 using the criteria of waist circumference [ 16 ], so measuring VFA itself rather than waist circumference is considered preferable for subsequent disease prevention.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in insulin-resistant patients, pancreatic fat content could favour a local pro-inflammatory environment and was negatively associated with insulin secretion [ 21 ]. Adipose tissue remodelling and inflammatory status following high fat intake are dependent on the lipid [ 22 ] and antioxidant [ 23 , 24 ] composition of the diets. In this context, specific local pro-inflammatory changes in pWAT after PO-rich diets may have systemic consequences regarding insulin resistance and glucose homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, we showed that serum carotenoids correlated inversely with several parameters of body fat composition, glucose regulation, and cardio-metabolic risk factors in humans. However, retinol did not correlate with any of these parameters [ 57 ].…”
Section: Discussionmentioning
confidence: 99%